In vivo Glioblastoma Therapy Using Targeted Liposomal Cisplatin - Ashrafzadeh MS (Dove Medical Press, 2020)
Maryam Sadat Ashrafzadeh,1 Azim Akbarzadeh,2 Amir Heydarinasab,1 Mehdi Ardjmand3 1Department of Chemical Engineering, Science and Research Branch, Islamic Azad University, Tehran, Iran; 2Department of Pilot Nanobiotechnology, Pasteur Institute of Iran, Tehran, Iran; 3Department of Chemical Engineering, South Tehran Branch, Islamic Azad University, Tehran, IranCorrespondence: Azim AkbarzadehDepartment of Pilot Nanobiotechnology, Pasteur Institute of Iran, Tehran, IranTel +989128387017Email azimakbarzadeh21@gmail.comBackground: Drug delivery systems have demonstrated promising results to cross blood–brain barrier (BBB) and deliver the loaded therapeutics to the brain tumor. This study aims to utilize the transferrin receptor (TR)-targeted liposomal cisplatin (Cispt) for transporting Cispt across the BBB and deliver Cispt to the brain tumor.Methods: Targeted pegylated liposomal cisplatin (TPL-Cispt) was synthesized using reverse phase evaporation method and thiolated OX26 monoclonal antibody. The formulation was characterized in terms of size, size distribution, zeta potential, drug encapsulation and loading efficiencies, bioactivity, drug release profile, stability and cellular uptake using dynamic light scattering, flame atomic absorption spectroscopy (AAS), ELISA, dialysis membrane, and ﬂuorescence assay. Next, the potency of the formulation to increase the therapeutic effects of Cispt and decrease its toxicity effects was evaluated in the brain tumor-bearing rats through measuring the mean survival time (MST), blood factors and histopathological studies.Results: The results showed that TPL-Cispt with a size of 157± 8 nm and drug encapsulation efficiency of 24%± 1.22 was synthesized, that was biologically active and released Cispt in a slow-controlled manner. The formulation compared to Cispt-loaded PEGylated liposome nanoparticles (PL-Cispt) caused an increase in the cellular uptake by 1.43-fold, as well as an increase in the MST of the brain tumor-bearing rats by 1.7-fold compared to the PL-Cispt (P< 0.001). TPL-Cispt was potent enough to cause a significant decrease in Cispt toxicity effects (P< 0.001).Conclusion: Overall, the results suggest that targeting the Cispt-loaded PEGylated liposome is a promising approach to develop formulation with enhanced efficacy and reduced toxicity for the treatment of brain tumor.Keywords: liposome, targeted drug delivery, brain tumor, blood brain barrier, cisplatin